UJI SENSITIVITAS ANTIBIOTIKA TERHADAP BAKTERI PENYEBAB INFEKSI PADA LUKA PASCA OPERASI - Mirza, Mirzan Hasibuan; Suharsih; Situmorang, Nurbaity; Novina Sukapiring, Dewi; Kusumawati, R Lia (Universitas Cokroaminoto Palopo, 2024)
Nosocomial infection is a systemic or local condition caused by a reaction to an infectious agent such as bacteria that occurs more than 48 hours after the patient is admitted to the hospital. One of the nosocomial infections is post-surgery wound infection which is a common problem that causes morbidity and mortality in hospitals. The challenge for doctors who treat infected patients is the accuracy of antibiotic therapy, which slows down the healing process of infection in postoperative wounds. This study aims to determine the sensitivity of antibiotics to bacteria that cause infections in post-surgery patient wounds which can be recommended as definitive therapy. This study is a retrospective cohort conducted descriptively during October 2020 with a total of 75 samples. The results of the study showed that antibiotic sensitivity to gram-negative bacteria was amikacin (91%), meropenem (81%), gentamycin (56%), ciprofloxacin (42%), cefepime (39%), cefoperazone sulbactam (39%), cotrimoxazole (28%), ceftazidime 25%, aztreonam (18%), ceftriaxone (14%), ampicillin-sulbactam (11%) and ampicillin (2%). Meanwhile, sensitivity to gram-positive bacteria is vancomycin (83%), linezolid (61%), gentamycin (61%), clindamycin (39%), erythomycin (39%), levofloxacin (33%), ciprofloxacin (28%), cotrimoxazole (22%) and ampicillin, cefotaxime, ceftazidime, ceftriaxone (17%), respectively. Antibiotics with a sensitivity of >80% that can be recommended as definitive therapy for post-operative wound infections are amikacin (91%) and meropenem (81%) for gram-negative bacteria and vancomycin (83%) for gram-positive bacteria.